Population Genetics of the Black Citrus Aphid Aphis aurantii (Hemiptera, Aphididae) in China - Liu, Hong-Ling; Chen, Zhi-Teng; Liu, Chao; Wu, Xing-Long; Xiao, Ke-Jun; Pu, De-Qiang (Frontiers in Ecology and Evolution, 2021)
The black citrus aphid, Aphis aurantii Boyer de Fonscolombe, 1841, is one of the most destructive pests in commercial tea plantations and gardens in China. In this study, we investigated the population genetic structure of A. aurantii based on the concatenated sequences of two mitochondrial genes, cytochrome coxidase I (cox1) and cytochrome b (cytb). A total of 166 haplotypes were identified from 177 individuals collected at 11 locations in China. The whole Chinese A. aurantii population showed a low nucleotide diversity (0.00968) and a high population diversity (haplotype diversity) (0.9991). The haplotypes of the 11 local populations were widely distributed in neighbor-joining phylogenetic tree and haplotype network diagram, whereas no apparent lineages were detected. Gene flow analysis showed gene exchanges among local populations. The pairwise Fst values revealed a certain amount of genetic difference among local populations. The analysis of molecular variance (AMOVA) reflected genetic differences both within and among populations. The IBD analysis revealed a high positive correlation between the geographic distance and genetic distance of different populations. Neutral test and mismatch distribution suggested A. aurantii may have experienced recent population expansion events.